1993
DOI: 10.2105/ajph.83.7.955
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital cardiac arrest: racial differences in outcome in Seattle.

Abstract: OBJECTIVES. Out-of-hospital sudden cardiac arrest is a key area in which to study the dual problem of the poorer health status of minority populations and their poorer access to the health care system. We proposed to examine the relationship between race (Black/White) and survival. METHODS. We determined the incidence and outcome of cardiac arrests in Seattle for which medical assistance was requested. RESULTS. Over a 26-month period, the age-adjusted incidence of out-of-hospital cardiac arrest was twice as gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
4
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 9 publications
3
84
4
4
Order By: Relevance
“…Our findings may differ from prior adult studies examining racial differences, given that our analysis was conducted using a more contemporary patient population as compared with many of the adult studies. Additionally, several prior studies have drawn patients from a single city or area of the country, whereas our study drew patients from a wide range of geographic locations and thus may be less susceptible to regional treatment bias 15, 17, 18. Lastly, unlike in adults where lower rates of bystander CPR among some racial groups have been implicated as a cause for worse outcomes, rates of bystander CPR in our study did not differ according to race.…”
Section: Discussionmentioning
confidence: 88%
“…Our findings may differ from prior adult studies examining racial differences, given that our analysis was conducted using a more contemporary patient population as compared with many of the adult studies. Additionally, several prior studies have drawn patients from a single city or area of the country, whereas our study drew patients from a wide range of geographic locations and thus may be less susceptible to regional treatment bias 15, 17, 18. Lastly, unlike in adults where lower rates of bystander CPR among some racial groups have been implicated as a cause for worse outcomes, rates of bystander CPR in our study did not differ according to race.…”
Section: Discussionmentioning
confidence: 88%
“…Blacks are disproportionately affected by SCD, and the increased risk is only partially explained by the higher prevalence of important clinical risk factors of left ventricular hypertrophy and hypertension [54][55][56]. Black hypertensive patients have an increased risk of SCD compared to whites, even after adjusting for multiple other risk factors [57].…”
Section: Sudden Cardiac Deathmentioning
confidence: 99%
“…[1][2][3][4][5][6] The age-adjusted incidence of out-ofhospital cardiac arrest is higher for blacks than for whites. 1,2 The initial resuscitation rate is much poorer, and the rates of survival to hospital discharge are much lower in blacks. 1,2 Several studies have shown that blacks have disproportionately high morbidity and mortality rates with respect to cardiovascular disease.…”
mentioning
confidence: 99%
“…1,2 The initial resuscitation rate is much poorer, and the rates of survival to hospital discharge are much lower in blacks. 1,2 Several studies have shown that blacks have disproportionately high morbidity and mortality rates with respect to cardiovascular disease. [3][4][5][6] Blacks have a higher mortality rate or increased risk of subsequent cardiac events after myocardial infarction than whites.…”
mentioning
confidence: 99%